Balancing and scheduling of car floor subassembly production flow line - Kays, H. M. Emrul (Kulliyyah of Engineering, International Islamic University Malaysia, 2015)
In a mass production environment where shared resources, restricted task assignments and parallel processing are present, the concept of line balancing and scheduling can play a pivotal role in framing optimal operational decisions. Though this approach is widely referred in OR and/or OM literature covering the individual issues of resource sharing, workstation paralleling, restricted task assigning, researches focusing on a comprehensive solution are rarely available. Hence, this study is undertaken to provide a broader approach based on an investigation of an automotive part or subassembly production flow line having all of the above mentioned issues. A process chart is portrayed on the basis of the time study and the relevant precedence matrix to articulate the current shop floor practices and a network diagram is prepared to identify the bottlenecks. Subsequently a balancing and scheduling model with binary integer programming is developed by considering the constraints from task assignment, positive zoning, cycle time, precedence relation, stage and workstation, with an objective to minimize the batch completion time. The developed mathematical model is designed in the spread sheet with 142 constraints, 102 decision variables and solved by the 'What's Best optimizer'. The obtained solution is assessed through different performance metrics including the risks and economic aspects. It is revealed that the proposed solution or approach minimizes the batch completion time with consequent increment in the production rate through assignment of the tasks in three stages with two additional parallel workstations. It is also observed that the completion time can be minimized in stage-1 by 20 minutes (through optimized scheduling and sequencing in the shared resources), by 2.73 hour in stage-2 (through workstation paralleling) and 3.17 hour in stage-3 (through workstation paralleling). Consequently, the production rate of the flow line is to be increased from 1.26 to 2.36 batches (i.e. from 189 to 369 units) per shift. However, as workstation paralleling incurs additional costs, an economic analysis is performed for the proposed approach in conservative view. It shows that the additional investment is to be recovered within about 7 months which is indeed much less than the useful life of the machine. The eventual outcome of this research work is likely to lead to formulate a balancing, scheduling and integrated inventory management model for the mixed and/or multi production environment.